(untitled) (Web of Teachers: Inderscience Research, 2025)
This article vividly highlights the early years of the Qamusi scholar Abu Rayhan Beruni, his interest in science, the scientist’s contribution to the development of world science, the scientific legacy and educational significance of his works.